Formulasi Sediaan Pomade dan Uji Efektivitas Ekstrak Daun Salam (Syzygium Polyanthum) terhadap Pertumbuhan Rambut Kelinci New Zealand White - Putri Barlian Nur Cahyaning Tyas; Bangkit Riska Permata; Rizka Wahyu Syahputra (Pusat Riset dan Inovasi Nasional, 2025)
Bay leaves are known to contain flavonoids, tannins, saponins, and essential oils, which have been empirically proven to promote healthy hair. This study aimed to determine the potential of bay leaf extract (Syzygium polyanthum) as an active ingredient in pomade and its effectiveness on hair growth in New Zealand White rabbits. The research method used was an experimental laboratory with four variations of pomade formulations: F0 (without extract), F1 (20%), F2 (25%), and F3 (30%). Evaluations were conducted on physical quality parameters such as organoleptic properties, pH, homogeneity, spreadability, viscosity, and adhesion. Effectiveness testing was conducted on the rabbits' backs for 28 days, measuring hair growth. The results of the study showed that pomade preparations with bay leaf extract had physical qualities that met the requirements for hair growth with various extract effectiveness on the 28th day of peak testing showing Formula I (20%) 0.4 cm, formula II (25%) 0.4 cm, Formula III (30%) 1.0 cm, providing the highest hair growth results, namely Formula III compared to other formulas. The results of SPSS statistical analysis with a significance value <0.05 resulted in differences between treatments. So it can be concluded that bay leaf extract can be formulated into an effective pomade preparation in stimulating hair growth.